The case for 'public' transport in the age of automated mobility. (September 2022) - Docherty, Iain; Stone, John; Curtis, Carey; Sørensen, Claus Hedegaard; Paulsson, Alexander; Legacy, Crystal; Marsden, Greg
Abstract: This paper highlights the extent to which a future mobility system dominated by Connected and Autonomous Vehicles (CAVs) poses profound challenges to the 'publicness' of the transport and mobility systems of many cities. This is evident at different policy levels: the regulatory posture of governments, changing notions of the contributions of mobility to wider 'public value', and the underpinning shared experiences of urban life and citizenship or civitas . There is relatively little discussion of how widespread automation might reduce the 'publicness' of transport systems in terms of the range of mobility opportunities they offer, how changing patterns of mobility across neighbourhoods and social groups will contribute to urban restructuring, and the implications of this for public value and the character or civitas of cities. In particular, we note how the huge expansion in mobility choices made possible by CAVs might lead to circumstances in which the outcome of individuals exercising that choice is to change the nature of urban mobility profoundly. We identify a number of key challenges that policy makers will need to address in managing the introduction of CAVs in their cities, and how using the lens of 'publicness' might help them do so. Highlights: We explore how the notion of 'publicness' can contribute to debates on how best to manage and govern the impacts of autonomous mobility Shared and automated mobility could extend or diminish opportunities for citizens, with multiple ramifications for public interests Policy makers are under intense pressure from varied interests over how best to regulate and govern automated mobility We conceptualise publicness as existing at three levels of debate: ownership and regulation, public value, and civitas Effective policy interventions will be required to achieve 'public' goals at each of these levels